Features of the development of innovative technologies in the field of solar energy - Abayev А.; Yessengeldin, B.; Shuren, T.K.; Kocherbayeva, A. (BUKETOV BUSINESS REVIEW, 2023)
Object:The purpose of the article is to study the effectiveness of innovative technologies in the field of solar energy. The article discusses the possibilities and prospects of using modern technologies for the development of solar energy. Method:The article uses systematic, analytical, generalizing, comparative and statistical methods for determining the effectiveness of innovative solar energy production technologies. These methods are based on the results obtained from official statistics on the development of solar energy, scientific concepts obtained in scientific articles by domestic and foreign scientists. Results:The article explores various technical and organizational issues of innovative development of solar energy: mechanisms for the introduction of thermoelectric solar installations; industry and operational parameters of technology; social, political and cultural aspects; financial and personnel support; infrastructure capabilities of the region or industry. During the analysis, technical problems of solar panels were identified: the appearance of microcracks due to weather conditions; dependence on the intensity of the sun; low efficiency of photovoltaic cells; high price of raw materials sources (silicon, silver, aluminum, copper and others); lack of research on recycling accumulated waste for reuse. Conclusions:The article provides recommendations for the production of solar energy, taking into account the accumulated international experience: the choice of solar panels based on economic efficiency and technical characteristics; the installation of technologies depending on the location and climatic conditions of the region; the use of effective methods of disposal of used solar panels; the implementation of state control over the implementation of measures to ensure the safety of solar energy generation.